Delineating chromatin accessibility re-patterning at single cell level during early stage of direct cardiac reprogramming. (January 2022) - Wang, Haofei; Yang, Yuchen; Qian, Yunzhe; Liu, Jiandong; Qian, Li
Abstract: Direct conversion of cardiac fibroblast into induced cardiomyocytes (iCMs) by forced expression of cardiac transcription factors, such as Mef2c, Gata4, and Tbx5 (MGT), holds great promise for regenerative medicine. The process of cardiac reprogramming consists of waves of transcriptome remodelling events. However, how this transcriptome remodelling is driven by the upstream chromatin landscape alteration is still unclear. In this study, we performed single-cell ATAC-seq (Assay for Transposase-Accessible Chromatin using sequencing) on early reprogramming iCMs given the known epigenetic changes as early as day 3. This approach unveiled networks of transcription factors (TFs) involved in the early shift of chromatin accessibility during cardiac reprogramming. Combining our analysis with functional assays, we identified Smad3 to be a bimodal TF in cardiac reprogramming, a barrier in the initiation of reprogramming and a facilitator during the intermediate stage of reprogramming. Moreover, integrative analysis of scATAC-seq with scRNA-seq data led to the identification of active TFs important for iCM conversion. Finally, we discovered a global rewiring of cis-regulatory interactions of cardiac genes along the reprogramming trajectory. Collectively, our scATAC-seq study and the integrative analysis with scRNA-seq data provided valuable resources to understand the epigenomic heterogeneity and its alteration in relation to transcription changes during early stage of cardiac reprogramming. Graphical abstract: Unlabelled Image Highlights: scATAC-seq revealed chromatin accessibility dynamics of early iCM reprogramming. Smad3 plays a bimodal role at different stages of iCM reprogramming. Fos, a subunit of AP-1, may function as a barrier to efficient iCM reprogramming. The cis-interactions of cardiac genes are rewired during early iCM reprogramming.